PERANCANGAN SISTEM INFORMASI RESEP PULANG FARMASI RAWAT INAP DENGAN METODE E-PRESSCRIBING PADA RS XYZ - Tb dedifuadi; Ahmad Surahmat; Rizki Fatullah (Journal of Innovation And Future Technology (IFTECH), 2021)
The Hospitals are one of the industries engaged in health services where hospitals are always required to have good, efficient, and quality services. Pharmacy services are one of the activities in hospitals that support quality health services, including affordable clinical pharmacy services for all levels of society, in this case the patient queue at the registration section because registration is done manually. because the dose must be calculated first before being formulated, so the waiting time for the prescription to go home is long. There is duplication of prescriptions or there is drug interaction in one prescription, so we have to confirm with the doctor first, there is a vacancy in the drug stock at the Inpatient Pharmacy, so we have to borrow drugs from another department first, if the other pharmacies don't have the stock of the drug, we have to call the doctor first to change the drug with the same indication, if the doctor doesn't want to change we are forced to buy medicine from outside, in a previous study by Dian Rakasiwi (JKOMA; 2018) in his journal mentioning the design of an e-prescribing system (electronic prescribing) or prescription electronically by using the codeigniter framework in the manufacture of drug prescriptions so that the drug redemption time is more effective and efficient. So that with the Design of Information Systems Waiting Time for Inpatient Pharmacy Discharge Prescriptions with the E-Presscribing Method at XYZ Hospital using the Waterfall method to describe the system, UML (Unified Modeling System) and MySQL are used as Web-based information data storage databases with Codeigniter as a framework, so that Hospitals can improve pharmacy services in terms of minimizing waiting time for prescriptions.